Establecimiento de la producción de hongos micorrízicos arbusculares (HMA) asociados al cultivo de papa nativa (Solanum spp.) a través de cultivos trampa - Guamán Ojeda, María Cristina (2024)
Arbuscular mycorrhizal fungi (AMF) are subterranean microorganisms crucial for plant nutrition, growth, resilience, and resistance to both abiotic and biotic stressors. AMF form symbiotic associations with approximately 80% of plant taxa, including Solanum spp., which includes potatoes. Potato cultivation ranks among the top four global crops, alongside rice, wheat, and maize. Therefore, this study aimed to propagate and characterize the morphological traits of AMF for use in native potato cultivation in Ecuador's Southern Sierra, covering the provinces of Loja, Azuay, and Cañar. Native potato root samples were evaluated for AMF colonization before being deployed as AMF bioinoculum. Subsequently, trap crops using chives as host plants were established, and AMF colonization was assessed after 12 weeks. Finally, AMF spores were characterized to identify AMF morphospecies. Results showed increased AMF colonization in the roots of field-sourced native potato plants using bioinoculum from Azuay province (90%), attributed to minimal chemical inputs. Conversely, maximal AMF colonization in chive roots from trap crops occurred with inoculum from Cañar province, correlating with soil preservation and microbial biodiversity, evidenced by the detection of 593 AMF spores per 100 g of soil. Additionally, twenty AMF morphospecies belonging to four genera were identified: Glomus, Acaulospora, Sclerocystis, and Scutellospora, with the genus Glomus predominating.